The Spike at Benefit Exhaustion in the Finnish Labor Market - Tomi Kyyrä; Hanna Pesola; Jouko Kullervo Verho (Institute of Labor Economics (IZA), 2017)
Many studies have found that the exit rate from unemployment increases in the vicinity of the exhaustion day of unemployment insurance benefits. The extent to which this "spike" is driven by job search behavior is important for assessing the distortionary effect of unemployment insurance. Card, Chetty and Weber (American Economic Review 2007; 97: 113-118) find a large spike in the exit rate from registered unemployment but only a very small spike in the job finding rate in Austria. We replicate their analysis using matched register data for Finland. We find a large spike also in the job finding rate at the time of benefit exhaustion, even though it is clearly smaller than the spike in the exit rate from unemployment benefits. In addition, we demonstrate difficulties in measuring the time to benefit exhaustion when the benefit entitlement can elapse at a reduced rate during activation measures or part-time working. Unless the remaining benefit entitlement is directly observed in the data, the resulting measurement error can lead to downward biased estimates of the spikes at benefit exhaustion.
Keywords: C41; J64; J65; 330; layoffs; unemployment insurance; hazard rates